Beyond Visual Acuity: Development of a Simple Test of the Slow-To-See Phenomenon in Children with Infantile Nystagmus Syndrome. (1st February 2021) - Weaterton, Ruaridh; Tan, Shinn; Adam, John; Kaur, Harneet; Rennie, Katherine; Dunn, Matt; Ewings, Sean; Theodorou, Maria; Osborne, Dan; Evans, Megan; Lee, Helena; Self, James
ABSTRACT: Purpose: Conventional static visual acuity testing profoundly underestimates the impact of infantile nystagmus on functional vision. The slow-to-see phenomenon explains why many patients with nystagmus perform well in non-time restricted acuity tests but experience difficulty in certain situations. This is often observed by parents when their child struggles to recognise familiar faces in crowded scenes. A test measuring more than visual acuity could permit a more real-world assessment of visual impact and provide a robust outcome measure for clinical trials. Methods: Children with nystagmus and, age and acuity matched controls attending Southampton General Hospital were recruited for two tasks. In the first, eye-tracking measured the time participants spent looking at an image of their mother when alongside a stranger, this was then repeated with a sine grating and a homogenous grey box. Next, a tablet-based app was developed where participants had to find and press either their mother or a target face from up to 16 faces. Here, the response time was measured. The tablet task was refined over multiple iterations. Results: In the eye-tracking task, controls spent significantly longer looking at their mother and the grating ( P < .05). Interestingly, children with nystagmus looked significantly longer at the grating ( P < .05) but not their mother ( P > .05). This confirmed a facial target was key to further development. The tablet-based task demonstrated that children with nystagmus take significantly longer to identify the target; this was most pronounced using a 3-min test with 12-face displays. Conclusion: This study has shown a facial target is key to identifying the time-to-see deficit in infantile nystagmus and provides the basis for an outcome measure for use in clinical treatment trials.